ANALISIS PERENCANAAN PENANGANAN ABRASI MENGGUNAKAN DINDING PENAHAN TANAH KANTILEVER DAN PONDASI BOREPILE - Alhafidz, Muhammad; Rosyad, Farlin (Fakultas Teknik Universitas Muhammadiyah Sumatera Barat, 2025)
Coastal abrasion, soil pressure and rainfall are factors that greatly affect slope stability in the coastal area ofNorth Bengkulu. This can cause landslides on the road body if no protection is provided on the slope. In this study, an analysis was carried out on the retaining wall plan starting from shear stability, rolling stability, soil bearing capacity and continued with the analysis of the borepile foundation permit using manual calculations, after which the analysis was continued using Plaxis 8.2 to determine the Global Safety Factor. The results of the study showed that the existing slope had a safety factor of 1.051 (Not safe) so that to meet the geotechnical requirements of SNI 8460: 2017, the slope reinforcement at this research location used a safety device, namely a retaining wall combined with a borepile foundation. The next stage is the analysis for the Global Safety Factor using Plaxis 8.2 modeling which shows that the reinforcement of the retaining wall combined with the borepile foundation has a safety factor of 2.387 (Safe). The retaining wall has a height of 7.5 meters and an additional 6 meters for selected embankments which are equipped with drainage and vegetation, then the drilled well has a depth of 6 meters and a diameter of 60cm.Keywords: Abrasion, Borepile Foundations, Plaxis 8.2, Retaining Wall, Safety Factor